Cambridge O level Islamiyat textbook for paper 2 - Nishat, Hammad ibn (Karachi : Bookmark, 2020)
The Cambridge O Level Islamiyat Textbook for Paper 2 provides students with a comprehensive overview of key topics essential for the exam. It covers the life of Prophet Muhammad (PBUH), his role in spreading Islam, and the leadership of the Four Rightly Guided Caliphs. The textbook also explores important events in Islamic history, such as the Battle of Badr and the Treaty of Hudaybiyyah, and delves into core Islamic beliefs like Tawhid, Risalah, and Akhirah. Additionally, it highlights Islamic ethical teachings, the importance of knowledge, and the role of Shariah in society, equipping students with the necessary knowledge for success in the exam.
Keywords: Islamiat : textbook; Cambridge : Paper 2